Game analysis of product-service integration - Heping Zhong (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: This paper aims at defining the value creation mechanism and income distribution strategies of product-service integration in order to promote product-service integration of a firm. Design/methodology/approach: This paper conducts researches quantitatively on the coordination mechanism of product-service integration by using game theory, and uses the methods of Shapley value and Equal growth rate to further discuss income distribution strategies of product-service integration. Findings: Product-service integration increases the total income of a firm and the added value of the income decreases as the unit price demand variation coefficient of products and services increases, while decreases as the marginal cost of products increases, decreases as the marginal cost of services increases. Moreover, the findings suggest that both income distribution strategies of product-service integration based on Shapley value method and Equal growth rate method can make the product department and service department of a firm win-win and realize the pareto improvement. The choice of what kind of distribution strategy to coordinate the actions between departments depends on the department playing dominant role in the firm. Generally speaking, for a firm at the center of market, when the product department is the main contributor to firm income, the service department will choose the income distribution strategy of product-service integration based on Shapley value method; when the service department is the main contributor to firm income, the service department will choose the income distribution strategy of product-service integration based on Equal growth rate method. Research limitations/implications: This paper makes some strict assumptions such as complete information, risk neutral, linear cost function and so on and the discussion is limited to the simple relationship between product department and service department. Practical implications: Product-service integration enables a firm to improve its total income. A firm should take appropriate income distribution strategies in order to promote the its product-service integration. Originality/value: This paper introduces game theory into the research of product-service integration for the first time and it has reached some valuable conclusions, which has opened up a new field of study in the product-service area.
Keywords: 650; game theory; product-service integration; shapley value; servitization